Comparative study of wound sequlae in layer closure and retention closure of midline laparotomy - D., Euvalingam; Nathan, Sendhil (International Surgery Journal, 2019)
Background: Layered closure of the abdomen has been considered to be ideal until recently however single layer mass (retention) closure technique, in which all the layers of the abdominal wall are closed in single layer is being increasingly used by surgeons. We conducted this study to analyze outcome measures in patients in whom wound closure was done by retention closure and layered closure. Methods: This was a prospective comparative study in which 60 patients undergoing elective or emergency laparotomy were included on the basis of a predefined inclusion and exclusion criteria. In 30 cases (50%) layer closure was done whereas in remaining 30 (50%) patients retention closure technique was used. Major outcome measures studied were time required for wound closure and post-operative complications. Results: Out of 60 studied cases there were 42 (70%) males and 18 (30%) females with M: F ratio of 1: 0.42.The time required for closure in layered suture group (group A) was 26.76±3.36 whereas in case of retention closure suturing it was 19.36±4.35. The difference was found to be statistically highly significant (p<0.0001). The complications rates were found to be statistically significantly higher in layer suturing (Group A) as compared to retention suture group (Group B). Conclusions: We conclude that retention suturing is preferable as compared to layered suturing in patients undergoing midline laparotomy in terms of time required for closure of wound and post-operative complication rates.